2010
DOI: 10.1177/1046496410377509
|View full text |Cite
|
Sign up to set email alerts
|

Members’ Openness to Experience and Teams’ Creative Performance

Abstract: Team composition based on personality has been found to have important effects on team outcomes. However, little is still known about the effect of team personality composition on team creativity. To this end, this study examined the relationship of team members’ openness to experience and team creativity. Results from a study with 31 graduate student teams suggest that openness to experience is significantly related to team creativity. Furthermore, teams that are diverse on openness to experience have the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
76
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 75 publications
3
76
1
Order By: Relevance
“…The association between cultural diversity and team creativity/innovation has attracted considerable research attention. Primary studies have reported varied correlations for this relationship (e.g., Gibson & Gibbs, ; Li, Lin, Tien, & Chen, ; Schilpzand, Herold, & Shalley, ; Stringfellow, ). Prior meta‐analytic reviews, which are based on limited samples ( k ≤ 8), have also reported mixed findings, with pooled effect sizes ranging from −0.18 to 0.16 (Bell, Villado, Lukasik, Belau, & Briggs, ; Stahl et al, ; van Dijk, van Engen, & van Knippenberg, ).…”
Section: Introductionmentioning
confidence: 99%
“…The association between cultural diversity and team creativity/innovation has attracted considerable research attention. Primary studies have reported varied correlations for this relationship (e.g., Gibson & Gibbs, ; Li, Lin, Tien, & Chen, ; Schilpzand, Herold, & Shalley, ; Stringfellow, ). Prior meta‐analytic reviews, which are based on limited samples ( k ≤ 8), have also reported mixed findings, with pooled effect sizes ranging from −0.18 to 0.16 (Bell, Villado, Lukasik, Belau, & Briggs, ; Stahl et al, ; van Dijk, van Engen, & van Knippenberg, ).…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive compilation of group FFM clusters on engineering design team performance in the literature is presented in [Ogot and Okudan (2006]). Schilpzand et al ( [2011]) found that graduate engineering and business student teams diverse in openness exhibited more creativity on their innovation management class project, as measured by existing creativity scales ( [Tierney and Farmer 2002]) and peer review. The hypothesis was that individuals high in openness promoted divergence and ideation while those low in openness promoted convergence and idea selection, both of which are necessary for team creativity.…”
Section: Introductionmentioning
confidence: 99%
“…One of the key factors influencing whether students are stimulated by peers’ ideas appears to be the originality of those ideas (Fink et al, ). In addition, students’ openness to experience (broad mindedness, curiosity and originality; Costa & McCrae, ) appears to promote acceptance of peers’ ideas (Baer, Oldham, Jacobsohn, & Hollingshead, ; Schilpzand, Herold, & Shalley, ). Students who are high in openness to experience have been shown to be more sensitive to peers’ ideas in group contexts; they have also been shown to pay more attention to external and surface‐unrelated information, and this information may foster creativity (Agnoli, Franchin, Rubaltelli, & Corazza, ; Luse, McElroy, Townsend, & DeMarie, ).…”
Section: Introductionmentioning
confidence: 99%